Ultrasmall Platinum Nanoparticles Supported Inside the Nanospaces of Periodic Mesoporous Organosilica with an Imidazolium Network: An Efficient Catalyst for the Aerobic Oxidation of Unactivated Alcohols in Water. Issue 5 (4th February 2016) - Karimi, Babak; Naderi, Zahra; Khorasani, Mojtaba; Mirzaei, Hamid M.; Vali, Hojatollah
Abstract: The imidazolium group inside the wall of a periodic mesoporous organosilica provides an excellent environment for the stabilization of ultrasmall Pt nanoparticles (<1.5 nm), and this allowed the formation of a catalyst system (i.e., Pt (NP) @PMO‐IL) with significant activity and recyclability in the selective aerobic oxidation of various alcohols in water at ambient pressure of oxygen. In particular, the catalyst exhibited high activity in the oxidation of unactivated primary alcohols and sterically encumbered secondary aliphatic alcohols, which remain challenging substrates for many catalytic aerobic protocols. Abstract : Aerobic work out : Platinum nanoparticles supported in the channels of periodic mesoporous organosilica with an imidazolium framework (Pt (NP) @PMO‐IL) is an excellent and recyclable catalyst for the selective aerobic oxidation of various alcohols in water at ambient pressure of oxygen. The catalyst exhibits high activity in the oxidation of challenging unactivated primary alcohols and sterically encumbered secondary aliphatic alcohols.